Genetic analysis of heptad-repeat regions in the G2 fusion subunit of the Junín arenavirus envelope glycoprotein - York, Joanne (2005)
The G2 fusion subunit of the Junín virus envelope glycoprotein GP-C contains two hydrophobic heptad-repeat regions that are postulated to form a six-helix bundle structure required for the membrane fusion activity of Class I viral fusion proteins. We have investigated the role of these heptad-repeat regions and, specifically, the importance of the putative interhelical a and d position sidechains by using alanine-scanning mutagenesis. All the mutant glycoproteins were expressed and transported to the cell surface. Proteolytic maturation at the subtilisin kexin isozyme-1/site-1-protease (SKI-1/S1P) cleavage site was observed in all but two of the mutants. Among the adequately cleaved mutant glycoproteins, four positions in the N-terminal region (I333, L336, L347 and L350) and two positions in the C-terminal region (R392 and W395) were shown to be important determinants of cell-cell fusion. Taken together, our results indicate that α-helical coiled-coil structures are likely critical in promoting arenavirus membrane fusion. These findings support the inclusion of the arenavirus GP-C among the Class I viral fusion proteins and suggest pharmacologic and immunologic strategies for targeting arenavirus infection and hemorrhagic fever.